THE EFFECT OF DRAGON FRUIT PEEL WATER EXTRACT IN DRINKING WATER ON CARCASS AND PHYSICAL COMPOSITION OF BROILER CARCASSES - I M. A., Rahastra; Sriyani, N.L.P; Dewi, G.A.M.K. (Jurnal Peternakan Tropika; Vol 11 No 2 (2023): Vol. 11 No. 2 Tahun 2023; May - August, 2023)
This study aimed to determine the effect of dragon fruit peel exstract in drinking water on the carcass physical composition of broiler carcasses. The research design use a completely randomized design (CRD) consisting of four treatments and four replications, each replication containing four broilers. The treatments give were drinking water without dragon fruit peel exstract (P0/control); drinking water with 2% dragon fruit peel exstract (P1); drinking water with 4% dragon fruit peel exstract (P2); drinking water with 6% exstract dragon fruit peel (P3). The variables observed were slaughter weight, carcass percentage, carcass physical percentage (bone, meat, skin and subcutaneous fat). The results showed that broiler given dragon fruit peel water exstract 2%, 4%, 6% into drinking water had no significant difference in slaughter weight, carcass physical percentage (bone, meat, skin and subcutaneous fat) (P>0, 05) but had a significant effect (P<0.05) on the carcass percentage of broiler compared to controls. Based on the results of this study, it can be concluded that the use of 2%, 4% and 6% dragon fruit peel water exstract into drinking water did not affect slaughter weight, carcass physical percentage (bone, meat, skin and subcutaneous fat), but effect on increase in carcass percentage of broiler. Keywords: broiler, dragon fruit peel, carcass physical composition